Analysis of Information Security, Privacy, and Legality of Use in Modern Digital Transformation - Nadya Lathifah Riady; Evy Nurmiati (Politeknik Aceh Selatan, 2026)
The rapid growth and pervasive integration of digital technology in global sectors have significantly increased the vulnerability of organizational data, placing a paramount importance on information security, privacy preservation, and strict legal compliance. This study aims to examine the systemic relationship between these three critical dimensions within modern digital ecosystems, identifying core vulnerabilities and assessing regulatory efficacy. The research employs a qualitative methodology through a systematic literature review of highly credible scientific publications indexed between 2022 and 2024. The empirical findings indicate that weak database encryption architecture, low user cybersecurity awareness, and inconsistent legal enforcement frameworks are the primary socio-technical factors contributing to massive data breaches and proliferating cybercrimes. Furthermore, strict alignment with contemporary data protection regulations plays an indispensable role in safeguarding user privacy and compelling organizations to adopt proactive security posturing. However, a significant enforcement gap remains between comprehensive legal provisions and practical execution capabilities, particularly within public institutions and small-scale business sectors. This study highlights the urgent need for integrated, triple-helix collaborative strategies that combine technological innovations, comprehensive institutional policy frameworks, and continuous user awareness education to build a secure, resilient, and trusted digital ecosystem.